2018
DOI: 10.3389/fimmu.2018.02781
|View full text |Cite
|
Sign up to set email alerts
|

Host Regulators of Liver Fibrosis During Human Schistosomiasis

Abstract: Liver fibrosis is a wound-healing process purposely aimed at restoring organ integrity after severe injury caused by autoimmune reactions, mechanical stress or infections. The uncontrolled solicitation of this process is pathogenic and a pathognomonic feature of diseases like hepatosplenic schistosomiasis where exacerbated liver fibrosis is centrally positioned among the drivers of the disease morbidity and mortality. Intriguingly, however, liver fibrosis occurs and progresses dissimilarly in schistosomiasis-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
85
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 105 publications
(146 reference statements)
2
85
0
3
Order By: Relevance
“…Schistosomiasis is a chronic and potentially lethal disease, and the disease morbidity is caused by schistosome eggs and not directly by adult worms (35). Liver fibrosis caused by S. mansoni and S. japonicum is one of the most severe complications in advanced schistosomiasis, which usually accompanies portal hypertension and hepatosplenomegaly, and sometimes it is fatal (36).…”
Section: Discussionmentioning
confidence: 99%
“…Schistosomiasis is a chronic and potentially lethal disease, and the disease morbidity is caused by schistosome eggs and not directly by adult worms (35). Liver fibrosis caused by S. mansoni and S. japonicum is one of the most severe complications in advanced schistosomiasis, which usually accompanies portal hypertension and hepatosplenomegaly, and sometimes it is fatal (36).…”
Section: Discussionmentioning
confidence: 99%
“…Schistosomiasis is a widespread parasitic disease and affects more than 200 million people in many developing countries in tropical and subtropical areas [1]. The schistosome egg-induced hepatic granulomatous response, which subsequently results in serious liver fibrosis, is central to the morbidity and mortality in patients with schistosomiasis [2]. Thus, the effective suppression of granulomatous response-trigger liver fibrosis is crucial for schistosomiasis treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Both in vivo and clinical studies focusing on S. japonicum infections revealed that hepatic stellate cells (HSCs) are the key drivers of hepatic brosis [35,37], via collagen production and deposition. Importantly, liver brosis presentations have the potential to evolve into liver cirrhosis or liver cancer in the future [38]. Several studies have assessed the role of gut microbiota in cirrhosis of different etiologies [11,16,39,40,41].…”
Section: Discussionmentioning
confidence: 99%